(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
The article analyzes Principles of diplomacy, the importance of soft power in world politics. Factros of American leadership. The impact of US policy on international relations. Historical stages of US politics. In this study, an attempt was made to shed light on the importance of soft power, which is very necessary for the countries of the world, and its role today. This scientific article describes the soft power position of the USA, which has the main influence in today’s system of international relations, and the impact of US policy on international relations. In addition, the importance of diplomacy and how the foreign policy mechanism of countries has developed in today’s globalization era is also explained. Impact of hard power and soft power on each other. The influence of ambassadors, who are the main mediators in diplomacy, on international relations was also briefly described in this article.